Cyber-securing our elections. Issue 1 (2nd January 2018) - Pope, Amy E.
ABSTRACT: The 2016 U.S. Presidential election highlighted the cybersecurity threat of hostile state interference in democratic processes. A large body of evidence has emerged demonstrating how Russian operatives hacked the Democratic National Convention and leaked sensitive documents to undermine voter trust; spread disinformation and propaganda to polarise and divide American citizens; and suppressed voters with targeted advertisements and paid trolls. But hostile interference is a global threat and there are lessons to be learned from the U.S. election that could enable faster and more effective responses by governments around the world. This paper describes three preventative measures: the development of norms around influence operations – at a minimum, between like-minded states; internal government restructuring for improved real-time decision-making; and innovative mechanisms for public-private cooperation through trusted intermediaries. While there is no straightforward solution to protecting democratic processes, governments can begin taking steps to secure future elections from influence operations.